Enhancing Preschoolers' Independence through Toilet Training: A Case Study of Two Daycares in Semarang City - Aadilah, Endear Dahlia Nur; Pranoto, Yuli Kurniawati Sugiyo (AL-ISHLAH: Jurnal Pendidikan, 2024)
Toilet training is one of the important efforts in improving the independence and personal hygiene of preschool children, especially in the context of thaharah values in Islam. This study aims to describe the efforts to improve thaharah and independence of preschool children through toilet training in two daycare centers in Semarang City. This research used a qualitative approach with a case study approach model. Data were collected through observation, in-depth interviews with educators, and documentation. The results showed that both daycare centers have integrated the values of thaharah in their toilet training programs. The approaches used include habituation, modeling, and the use of language that is suitable for children's understanding. In addition to increasing independence in toilet use, the toilet training program also succeeded in fostering children's awareness of the importance of maintaining personal hygiene in accordance with religious teachings. Challenges faced in implementing toilet training include differences in children's characteristics, lack of parental support, and limited facilities. This study contributes to the development of toilet training programs that are oriented towards religious values. Recommendations include the importance of collaboration between educators, parents, and religious leaders in instilling the values of thaharah from an early age. In addition, it is necessary to develop a more comprehensive curriculum that integrates cognitive, affective, and psychomotor aspects in the toilet training process.